Prescribing Pattern and Rational use of Drugs in Al-Basrah Governorate Retail Pharmacies, Iraq - Haydar Fakhri Hadi Al Tukmagi (College of Pharmacy / Mustansiriyah University, 2013)
This study was designed to investing the drug prescribing pattern, the important factor to determine the rational or irrational use of drugs among patients dispensing their prescriptions from the private pharmacies in Al-Basrah governorate, Iraq for a period of 1 month. The data collected from prescriptions were calculated and analyzed according to the WHO prescribing guidelines. The data showed that the mean of drugs included in single prescription was 4%, and 13% of prescribed drugs were written as generic names; moreover, the percentage of antibiotics, corticosteroids and anxiolytics were 45.7%, 12% and 19.3% respectively. Those results indicate the irrationality of prescribing drugs when compared with the world health organization standard values of prescribing indicators; in addition to the bad prescribing pattern regardless of the degree of specialization of the physician, were 61% of those prescriptions have been written by specialized physicians. In conclusion, actual intervention and follow up, training on rational use of drugs and intervention strategies for prescribers is required to improve the rational use of drugs.